PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI PROBLEM BASED LEARNING PATA MATA PELAJARAN BIOLOGI KELAS X SMAN 1 KETUNGAU HULU - JOHNLI ALFATH (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
The purpose of this study was to increase students' learning motivation through a problem-based learning model in biology class X MIA SMAN 1 Ketungau Hulu. The subjects of this study were 35 class X MIA students at SMAN 1 Ketungau Hulu. This research is a classroom action research with two cycles. Based on the data analysis and discussion in IV, it can be concluded that the use of the PBL model can increase students' learning motivation in the material "virus" in biology class X MIA SMAN 1 Ketungau Hulu. This conclusion is based on an average increase in learning motivation. Students' learning motivation in the pre-cycle was 39.7 and included in the low criteria. Whereas in cycle I, the average value obtained was 61.9 and included in the high criteria. from pre cycle to cycle I there was an increase of 22.2. In cycle II the average value of students' learning motivation is 81.9 and is included in the very high criteria. From cycle I to cycle II there was an increase of 20. ABSTRAKTujuan dari penelitian ini adalah untuk meningkatkan motivasi belajar peserta didik melalui model pembelajaran problem based learning mata pelajaran biologi kelas X MIA SMAN 1 Ketungau Hulu. Subjek penelitian ini adalah peserta didik kelas X MIA SMAN 1 Ketungau Hulu yang berjumlah 35 orang. Penelitian ini adalah penelitian tindakan kelas dengan dua siklus. Berdasarkan analisis data dan pembahasan pada IV, maka dapat diambil kesimpulan bahwa penggunaan model PBL dapat meningkatkan motivasi belajar peserta didik pada materi "virus" mata pelajaran biologi kelas X MIA SMAN 1 Ketungau Hulu. Kesimpulan ini didasarkan adanya peningkatan rata-rata motivasi belajar. Motivasi belajar peserta didik pada pra siklus adalah 39,7 dan masuk dalam kriteria rendah. Sedangkan pada siklus I, nilai rata-rata yang diperoleh adalah 61,9 dan masuk dalam kriteria tinggi. dari pra siklus ke siklus I terjadi peningkatan sebanyak 22,2. Pada siklus II nilai rata-rata motivasi belajar peserta didik adalah 81,9 dan masuk dalam kriteria sangat tinggi. Dari siklus I ke siklus II terjadi peningkatan sebanyak 20.